Uv inscribed long period gratings with femtosecond ablated axial fibre slots for polarization control - Kalli, Kyriacos; Davies, Edward M.; Allsop, Thomas P.; Zhang, Lin; Koutsides, Charalambos (My University, 2011)
We present data on the development a new type of optical fibre polariser and the characterisation of its wavelength properties. The device is fashioned using a two step process. Firstly, a standard UV long period grating (LPG) with a period of 330μm is inscribed into hydrogenated SMF-28, followed by femtosecond laser ablation of a groove parallel to the fibre axis. The UV inscribed LPGs have inherently low birefringence. However, the removal of the cladding layer parallel to the location of the LPG within the fibre core (as a result the ablation) modifies the cladding modes that couple with the LPG. Furthermore, the groove breaks the fibre symmetry introducing a non-uniform stress profile across the fibre cross section leading to significant birefringence. We show that increasing the depth of the groove increases the birefringence, and this behaviour coupled with the ability to control the wavelength location of the LPGs attenuations peaks results in a polariser able to operate at almost any wavelength and birefringence. The maximum birefringence reported here as polarisation mode splitting was approximately 39±0.1nm with a polarisation loss of 10dB.
Keywords: Femtosecond lasers; Optical fibers; Optical instruments; Polarization